Strategy for Improving the Quality of Public Services Through Good Governance - Yanuarita, Heylen Amildha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The Indonesian government has obligations, one of which is public services in an effort to meet the needs of the community, provide fair services, and improve the welfare of citizens. Quality services play an important role in building public trust in government, especially at levels of government that are closer to the community, such as urban villages. The ideal condition in the implementation of good governance and public services is the fulfillment of all aspects that become service standards effectively, efficiently, and oriented towards community satisfaction. In Kelurahan Blabak, Kecamatan Pesantren Kota Kediri, various public services that are often provided face challenges in terms of quality and responsiveness. This research method uses a qualitative approach that describes improving the quality of public services through good governance with the theory of strategy from Osborne and Plastrik which consists of; Core Strategy, Consequences Strategy, Customer Strategy, Control Strategy, Culture Strategy. The results showed that the strategy of improving the quality of public services through good governance in Blabak Village, Pesantren Subdistrict, Kediri City is running quite well.